IMPACT OF LIMITED ORAL ANTITUBERCULOSIS INFORMATION TO THE TUBERCULOSIS PATIENTSâ COMPLIANCE AND THEIR QUALITY OF LIFE - Perwitasari, Dyah Aryani (PHARMACIANA, 2013)
The study about impact of limited oral antituberculosis information delivered by pharmacist to patient compliance and their quality of life in two public health centers inYogyakarta has been carried out. This study was performed using cohort event monitoring design, with 14 pulmonary TB patients and positive Acid Resistant Basil were treated with oral antituberculosis (OAT) for at least 1 month and were older than15 years old. We observed the compliance of one group of patients using oral antituberculosis who were serviced with OAT information and the other group without OAT information service. The patientsâ compliance was checked by counting theremaining OAT and by interviewing the patients, meanwhile patientâs quality of life were measured by SF-36 instrument. The correlation between limited OAT information service and patient compliance were analysed using Chi Square and quality of patientâs life were analysed using Independent t-Test with 95% confidence level. It was shown that characteristics of patients such as age, gender, education, duration of illness, andDirectly Observed Treatment involvement did not influence patient compliance. There was no significant correlation between limited OAT information service to patient compliance and patientsâ quality of life (P>0.05). There is no impact of limited OAT information service to the TB patientsâ compliance and their quality of life. We suggested that the further and deeply information service delivered by pharmacists in the public helath centers in Yogyakarta should be carried out.